Zika virus incidence, preventive and reproductive behaviors: Correlates from new survey data - Quintana-Domeque, C; Raimundo Carvalho, J; de Oliveira, V (Elsevier, 2018)
During the outbreak of the Zika virus, Brazilian health authorities recommended that pregnant women take meticulous precaution to avoid mosquito bites and that women in general use contraceptive methods to postpone/delay pregnancies. In this article, we present new estimates on the Zika virus incidence, its correlates and preventive behaviors in the Northeast of Brazil, where the outbreak initiated, using survey data collected between March 30th and June 3rd of 2016. The target population were women aged 15-49 in the capital cities of the nine states of the Northeast region of Brazil. We find that more educated women were less likely to report suffering from Zika (or its symptoms) and more likely to report having taken precaution against Zika, such as having used long and light-colored clothes, having used mosquito repellent or insecticides, having used mosquito protective screens or kept windows closed, and having dumped standing water where mosquitoes can breed. In addition, more educated women were more likely to report being informed about the association between Zika and microcephaly and to avoid pregnancy in the last 12 months. Finally, we also find that women who reported experiencing sexual domestic violence in the last 12 months were more likely to report suffering from Zika.